OBJECTIVE VERBAL & NON-VERBAL REASONING - OSWAAL (AGRA OSWAAL BOOKS & LEARNING PVT LTD, 2025)
This book is a an exhaustive question bank and study aid created to help aspirants master the reasoning sections of major competitive exams like SSC (CGL, CHSL), IBPS (Bank PO, Clerk), RRB (Railways), UPSC, NDA, and others. It is not a theoretical textbook but a practice-focused guide that breaks down the subject into two core parts: Verbal Reasoning (logic problems based on language) and Non-Verbal Reasoning (logic problems based on images, patterns, and diagrams). Its main purpose is to build speed and accuracy by providing a massive collection of over 2000+ practice questions, including previous years' questions, which are categorized chapter-wise, topic-wise, and by three difficulty levels (Beginner, Intermediate, Advanced). The book's structure is built around "Concept Clarity" (using solved examples to explain methods) and "Crisp Revision" (using tools like Mind Maps) to help students quickly review and effectively practice for their target exam.
VERBAL REASONING
COMPETITIVE EXAMS
Keywords: COMPETITIVE EXAMS